Infective Endocarditis: Updated Guidelines. Issue 2 (2010) - Allen, U
Abstract : The most recent revision of the American Heart Association guidelines on infective endocarditis prophylaxis occurred in 2007. These revisions were based on the fact that current data have brought into question the benefit of previous recommendations for infective endocarditis prophylaxis. It was noted that the bacteremia that occurs following dental procedures represents only a fraction of the episodes of bacteremia that occur with activities of daily living (such as chewing, brushing teeth and other oral hygiene measures). The target groups and the procedures for which prophylaxis is reasonable have been significantly reduced in number. The focus is now on patients who are most likely to have adverse outcomes from infectious endocarditis. The present article is targeted at practicing Canadian physicians and provides the rationale for the current recommendations. In addition to a summary of the indications for prophylaxis, information is provided on the conditions for which prophylaxis is not recommended.